The Impact of the Existence of PT Nusa Ina Company on the Socio-Economic Life of the Siliha Hamlet Community, North Seram Timur Kobi District - Ilela, Martencis; Pinoa, Wiclif Sepnath; Manakane, Susan Evelin (Jurnal Pendidikan Geografi Unpatti, 2023)
The existence of a company in society is a manifestation of participation in improving and developing community development. The problem in this study is determining the impact of the existence of PT Nusa Ina on the social life of the people of Dusun Siliha, Seram Utara Timur Kobi district. This research was conducted in Siliha hamlet, north Seram district, east Kobi, in October-November 2022. The purpose of this research was to find out the impact of the existence of the company PT Nusa Ina on the social life of the people of Siliha hamlet. The research method used is descriptive qualitative with an interactive analysis model: data reduction, data presentation, and conclusion. The subjects in this study were 20 people who worked in the company. The variables used are the company's existence and the community's social life. The social life of the Dusun Siliha community is seen from the level of education. Education in Dusun Silica is meant to increase with an average high school and tertiary level of education because, after the PT Nusa Ina company, community education only went up to elementary school, and few reached high school level. After PT Nusa Ina company, the community could finally send their children to tertiary education. Most of the monthly income from the community is more than Rp. 2.000.000, which is relatively high in terms of income. Then, the health condition of the people of Dusun Siliha before and after the existence of the PT Nusa Ina company was quite good. Ownership of living facilities is seen in owning electronic devices and motorized vehicles; most people already have them.